Mite Sanghyang Kenit: Daya Tarik Wisata Alam di Desa Rajamandala Kulon Kabupaten Bandung Barat - Isnaini, Heri; Indra Permana; Riana Dwi Lestari (Yayasan Literasi Sains Indonesia, 2022)
The stories that traditional societies believe in that have developed and spread over the generations have given birth to the concept of collective memory and belief. These memories and beliefs manifest into myths. In many traditions of indonesian society, myth is born from mite, a story that involves the supernatural power, namely the power of the Gods. In Sundanese culture, mites often tell the story of the Gods who descended to earth with a certain mission. This study discusses the Sanghyang Kenit mite which used to be considered a sacred story. Mite Sanghyang Kenit is discussed in a dual perspective, namely as a story of the past and as a cultural artifact that manifests as a tourist destination. The method used in this study is descriptive qualitative with the object of the story as data. In addition, SWOT matrices (strenghts); (weaknesses); (opportunities); and (threats) are used to analyze Sanghyang Kenit as a tourist destination in terms of uniqueness, authenticity, and scarcity. The results showed that Sanghyang Kenit mite can be a natural tourist attraction in Rajamandala Kulon village, West Bandung regency, namely by proving the existence of continuity between mites and potential tourist attractions.